PENGEMBANGAN MODEL PENGELOLAAN SEKOLAH DASAR BERBASIS MASYARAKAT BAGI PENINGKATAN KEMANDIRIAN SEKOLAH : Studi Pada Sekolah Dasar-Sekolah Dasar di Kabupaten Sumedang - Dady Muhtadi, - (2005)
This research is based on aroused problems related to the ineffective function of the elementary school management as required by the MPMBS purposes, and entitled 'The Improvement of Education through Promoting Independence Schooling in Managing and Empowering Its Available Resources'. To overcome this ineffective function problem, the research has been designed to and aimed at improving the school management models based on society participation and the impact of the model to the school independence especially in organizing the effective function of the whole available resources within the school. The study focuses on the society participation in every level of school activities, beginning from planning, implementation, as well as supervising programs arranged by the elementary school.This study is implemented under these major principles: School Based Management, Community Based Education as well as Site Based Management.To examine the hypothesis, this research uses two analysis models, namely, corelationa! deskriptive analysis and variabels is done test using apparent experiment. Data collecting deals with research variables is done thorugh spreading questionnaire, interview, and documentation study. The research of experimental special test is meant especially to school independence variable. The research of Corelation involves 100 persons as sample, which comprises school committee, Education Council, Student Parent, Headmaster, and Teachers. Two elementary school in Sumedang Region are determined to be the experimental research. Analysis techniques used in this case are: regression analysis, Corelation, and t-test.The result of this study in general concludes: (1) the society participation in managing the elementary school is proved significantly that it can improve the school independence in exploiting the available resources at school. This condition is supported by the increase of the contribution of society participation in planning, implementation, and observation of the elemantary school program. (2) The increase of society participation in managing the elementary school especially the participation in planning, implementation, and observation of the elementary school program either together or separated is supposed to be able to improve the elementary school independence in exploiting the available resources at school. (3) The result of the experimental research proves empirically that the management of the elementary school based on society, which in developed by this study, is proved effective in improving the school independence in exploiting the available resources at school.This study model is designed conseptually to develop substantial aspects based on the development of the elementary school management base on society. In the substansial frame of the supported power of the factual research gives basic direction in arrangement and conceptual development as a model of the improvement of school independence in exploiting the available resources at school. Therefore, the model of the elementary school management based on society, which is developed by this study, functionally has logical base (epistemologies) and also has great advantages (axiology) in its applicability.